Akulturasi Budaya Islam dan Jawa dalam Slawatan Ngelik - Sukatriningsih (Program Studi Pendidikan Sejarah - Universitas Samudra, 2024)
Abstract Slawatan ngelik or Javanese shalawat ngelik is an acculturative Javanese Islamic performance art in the form of the practice of reading shalawat Barzanji with local nuances characterized by Javanese langgam in terms of rhythm, accent, technique (ngelik), and instruments. Slawatan ngelik is also the core procession in the Muludan tradition in Kauman community. The purpose of this research is to find out the forms of acculturation that exist in slawatan ngelik. This research is a field research with descriptive qualitative research method. Data collection techniques consist of observation, interviews, and documentation. The approach used is cultural anthropology. The results show that slawatan ngelik contains elements of Islamic culture, namely, the tradition of Maulid Nabi and slawatan with the activity of reading the book Maulid al-Barzanji combined with elements of Javanese culture, namely, Javanese-style macapat rhythm with ngelik technique (high voice), musical instruments, and players consisting of gladen and panjak. This combination shows that slawatan ngelik is an Islamic-Javanese folk performance art. Keywords: acculturation, art, slawatan ngelik Abstrak Slawatan ngelik atau shalawat Jawa ngelik ialah seni pertunjukan Islam Jawa akulturatif berupa praktik membaca shalawat Barzanji bernuansa lokal dengan ciri khas langgam Jawa dari segi irama, logat, teknik (ngelik), dan instrumennya. Slawatan ngelik juga menjadi prosesi inti dalam tradisi Muludan di masyarakat Kauman. Tujuan dari penelitian ini adalah mengetahui bentuk-bentuk akulturasi yang ada dalam slawatan ngelik. Penelitian ini berjenis lapangan (field research) dengan metode penelitan deskriptif kualitatif. Teknik pengumpulan data terdiri dari observasi, wawancara, dan dokumentasi. Pendekatan yang dipakai adalah antropologi budaya. Hasil penelitian menunjukkan bahwa slawatan ngelik memuat unsur-unsur budaya Islam yaitu, tradisi Maulid Nabi dan slawatan dengan aktivitas pembacaan kitab Maulid al-Barzanji yang berpadu dengan unsur-unsur budaya Jawa yaitu, irama berlanggam Jawa ala macapat dengan teknik ngelik (suara tinggi), instrumen karawitan, dan pemain yang terdiri dari gladen serta panjak. Perpaduan ini menunjukkan kalau slawatan ngelik merupakan seni pertunjukan rakyat bernafaskan Islam-Jawa. Kata kunci : akulturasi, kesenian, slawatan ngelik